The current situation in childhood hearing screening in our country and around the world [Çocukluk dönemi işitme taramalarinda ülkemizde ve dünyada güncel durum] - (:unkn) unknown (Cocuk Sagligi ve Hastaliklan Dergisi, 2014)
Hearing loss is the most prevalent developmental disorder. Early identification of hearing loss and provision of early intervention services within the first six months of life have been demonstrated to facilitate normal or near-normal language acquisition. The purpose of this review is to evaluate the current situation regarding hearing screening in our country and around the world. Hearing screening during the neonatal period has an important impact on child health but also entails some important drawbacks. It is important to refer infants who fail hearing screening tests for further evaluation, and to ensure prompt early rehabilitation. Screening programs should not be limited to the neonatal period, and ongoing screening should be continued at the intervals recommended by the guidelines.
Keywords: Hearing loss; Hearing screening; Newborn; Preschool; School age